Programmatic mapping and size estimation of key populations to inform HIV programming in Tanzania - Wambura, Mwita (PLoS One, 2020)
INTRODUCTION: A programmatic mapping and size estimation study was conducted in 24 districts in 5 regions of Tanzania to estimate the size and locations of female sex workers (FSW) and men who have sex with men (MSM) to inform the HIV programming for Key Populations. METHODOLOGY: Data were collected at two levels: first, interviews were conducted with informants to identify venues where FSWs and MSM frequent. Secondly, the size of MSM and FSWs were estimated through interviews with FSWs, MSM and other informants at the venue. The venue estimates were aggregated to generate the ward level estimates. Correction factors were then applied to adjust for MSM/FSW counted twice or more, absent from the venues on the mapping day or remain online and hidden. The ward size estimates for mapped wards were extrapolated to non-mapped wards and aggregated to generate district and regional level estimates. RESULTS: A total of 4,557 level I interviews were conducted. Further, 3,098 FSWs and 1,074 other informants at the FSWs venues and 558 MSM and 210 other informants at the MSM venues were interviewed during level II. The mapping survey identified 6,658 FSW, 1,099 FSW and MSM and 50 MSM venues in 75 wards. A total of 118,057 (range: 108,269 to 127,845) FSWs and 23,771 (range: 22,087 to 25,454) MSM were estimated in the study regions after extrapolation and accounting for correction factors. It was estimated that 5.6% and 1.3% of the female and male population of reproductive age (15–49 years old) could be FSWs and MSM in the study regions, respectively. CONCLUSION: This study provides the baseline figures for planning, target setting and monitoring of the HIV intervention services in the study areas and geographic prioritisation of the response by allocating more resources to areas with a large number of FSWs and MSM.